Effectiveness of Tongue-lip Adhesion for Obstructive Sleep Apnea in Infants with Robin Sequence Measured by Polysomnography. (September 2016) - Resnick, Cory M.; Dentino, Kelley; Katz, Eliot; Mulliken, John B.; Padwa, Bonnie L.
Objective: Tongue-lip adhesion (TLA) is commonly used to relieve obstructive sleep apnea (OSA) in infants with Robin sequence (RS), but few studies have evaluated its efficacy with objective measures. The purpose of this study was to measure TLA outcomes using polysomnography. Our hypothesis was that TLA relieves OSA in most infants. Methods: This is a retrospective study of infants with RS who underwent TLA from 2011 to 2014 and had at least a postoperative polysomnogram. Predictor variables included demographic and birth characteristics, surgeon, syndromic diagnosis, GILLS score, preoperative OSA severity, and clinical course. A successful outcome was defined as minimal OSA (apneahypopnea index score < 5) on postoperative polysomnogram and no need for additional airway intervention. Descriptive, bivariate, and regression statistics were computed, and statistical significance was set at P < .05. Results: Eighteen subjects who had TLA at a mean age of 28 ± 4.7 days were included. Thirteen (72.2%) had a confirmed or suspected syndrome, and the mean GILLS score was 3 ± 0.3. All parameters trended toward improvement from the preoperative to postoperative polysomnograms, and improvement in OSA severity, oxygen saturation nadir, and arousals per hour was statistically significant ( P < .02). This effect was significant across categories of surgeon, syndrome, and GILLS score. Nine subjects (50%) met the criteria for a successful outcome. Bivariate and regression analyses did not demonstrate a significant relationship between success and any predictor variable. Conclusions: TLA improved airway obstruction in all infants with RS but resolved OSA in only nine patients, and success was unpredictable.